A sulfur cobalt bimetallic composite material rich in sulfur vacancies and application thereof to degradation of new pollutants

CN122999224APending Publication Date: 2026-10-30YUNNAN YUNCE QUALITY INSPECTION CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611292445.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-25
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

然而,单一铁碳复合材料中铁循环速率仍有待进一步提升,且碳材料表面活性位点类型与密度有限,难以满足新污染物高效治理的实际需求

Benefits of technology

(1)本发明采用可溶性淀粉作为分散剂与碳源,通过共沉淀-陈化耦合高温热解策略,实现了Fe3O4纳米颗粒在碳基质上的高度分散,有效抑制了颗粒团聚,增加了活性位点的暴露程度;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122999224A_ABST
    Figure CN122999224A_ABST
Patent Text Reader

Abstract

The application discloses a sulfur cobalt bimetallic catalyst rich in sulfur vacancies, which is prepared by mixing oxalic acid, soluble starch and deionized water, dropping a ferrous sulfate solution into the mixed solution, aging in a water bath, and washing, filtering and drying the product to obtain a ferrous oxalate precursor containing starch. The precursor is calcined at 500 DEG C for 2h under a nitrogen atmosphere to obtain a Fe3O4@SC composite catalyst in situ. The Fe3O4@SC is dispersed in ethylene glycol, and cobalt acetate and different amounts of thiourea are added, and then the mixture is ultrasonically dispersed and transferred to a reaction kettle for hydrothermal reaction at 200 DEG C, and the CoS / Fe3O4@SC composite catalyst is prepared after filtration and drying; the material has high catalytic activity, excellent magnetic separation performance and good structural stability, and is rich in oxygen vacancies Ov and sulfur vacancies Sv and other advantages, and can be widely used for degrading new pollutants, and has good degradation and removal effects. The application realizes utilization of advanced oxidation catalytic materials, and has great application prospect in the field of environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of advanced oxidation catalysis technology, specifically relating to a sulfur-cobalt bimetallic composite material rich in sulfur vacancies and its application in degrading new pollutants. Background Technology

[0002] New pollutants refer to toxic and hazardous chemical substances that possess characteristics such as biotoxicity, environmental persistence, and bioaccumulation, posing significant risks to the ecological environment or human health, but which are not yet included in environmental management or where existing management measures are insufficient. Currently, new pollutants of widespread concern both domestically and internationally mainly fall into four categories: persistent organic pollutants (POPs), endocrine disruptors (EDCs), antibiotics, and microplastics. Among these, antibiotics, as a typical new pollutant, have attracted considerable attention due to their long-term and extensive use. Of the many antibiotics, tetracycline antibiotics, represented by tetracycline hydrochloride (TC), chlortetracycline (CTC), and oxytetracycline (OTC), are widely used in clinical medicine and livestock farming due to their broad-spectrum antibacterial activity and low cost. However, these antibiotics are difficult to completely metabolize in humans and animals; approximately 40% to 90% enter the environment in the form of the original drug or active metabolites through excrement, persistently remaining in soil, surface water, and groundwater. New pollutants pose a serious threat to both the ecological environment and human health, with their harm being long-term, cumulative, and potential. In terms of the ecological environment, new pollutants disrupt the ecological balance. These pollutants accumulate in soil, water, and organisms over long periods, leading to a decline in biodiversity. Persistent organic pollutants can cause decreased reproductive capacity and impaired immune systems in wild animals, affecting population reproduction; the overuse of antibiotics can disrupt the structure of soil and aquatic microbial communities, altering the function and stability of ecosystems. For human health, the threat posed by emerging pollutants is particularly significant. Long-term low-dose exposure may lead to reproductive disorders, developmental delays, decreased immune system function, neurobehavioral abnormalities, and even cancer.

[0003] Existing new pollutant treatment technologies mainly include biological methods, physical adsorption, membrane separation, and advanced oxidation processes. While biological methods (such as activated sludge processes and microbial degradation) are simple to operate, they can easily lead to microbial community imbalance when treating high-concentration antibiotic wastewater, and their degradation efficiency is limited. Physical adsorption only transfers pollutants from the liquid phase to the solid phase, failing to achieve complete mineralization, and faces difficulties in adsorbent regeneration and secondary pollution problems. Although membrane separation has high retention efficiency, its operating costs are high, and membrane fouling is severe, limiting its application, especially in the treatment of high-concentration wastewater.

[0004] Advanced oxidation processes (AOPs) based on persulfate (PMS) can generate SO4. - •,•OH and 1O2 and other highly reactive oxygen species exhibit significant advantages in the degradation of novel pollutants, possessing strong oxidizing power, a wide applicable pH range, and mild operating conditions. However, PMS itself decomposes slowly, requiring efficient catalysts for rapid activation. Among numerous heterogeneous catalysts, magnetic iron(III) oxide (Fe3O4) has been widely studied due to its combination of catalytic activity and magnetic separation and recovery capabilities. However, Fe3O4 nanoparticles are prone to aggregation, and their surface Fe... 3+ / Fe 2+ The slow redox cycle rate severely limits the sustained activation efficiency of PMS. To overcome this deficiency, an attempt was made to composite Fe3O4 with carbon materials, utilizing the high conductivity and large specific surface area of ​​the carbon matrix to suppress particle agglomeration and promote electron transfer. Carbon materials can not only act as electron transport channels to accelerate Fe... 3+ To Fe 2+ The reduction of carbon can also directly participate in the activation of PMS through its surface defects and oxygen-containing functional groups, thereby achieving synergistic degradation through both free radical and non-free radical pathways. However, the iron cycling rate in single iron-carbon composite materials still needs to be further improved, and the types and density of active sites on the surface of carbon materials are limited, making it difficult to meet the actual needs of efficient treatment of new pollutants.

[0005] Cobalt sulfides (CoSx) in transition metal sulfides have become a research hotspot in PMS activation in recent years due to their excellent conductivity and abundant redox active sites. By constructing Fe / Co bimetallic composite catalysts, the synergistic redox cycle between the two metal ions can significantly accelerate electron transfer, thus compensating for the slow iron cycle in single iron-based materials. Furthermore, low-valence sulfur species in transition metal sulfides (such as CoS) possess strong reducing power and can act as electron donors to further promote the regeneration of metal active centers. In recent years, defect engineering has also shown unique advantages in improving catalytic performance, particularly oxygen vacancies (O2). v ) and sulfur vacancies (S v It can act as an electron trapping center, lowering the reaction energy barrier and accelerating interfacial charge transfer, while promoting the adsorption and activation of reactants (such as PMS and O2) on the catalyst surface. Summary of the Invention

[0006] This invention provides a sulfur-vacancy-rich cobalt-sulfur bimetallic composite material, which is prepared by mixing oxalic acid, soluble starch, and deionized water, stirring and mixing at 55-65°C, adding ferrous sulfate solution dropwise, aging in a water bath at 55-65°C, separating the solid and liquid phases, washing and drying the solid product to obtain a starch-containing ferrous oxalate precursor; calcining the precursor at 450-550°C for 1-3 hours under a nitrogen atmosphere to obtain a Fe3O4@SC composite; dispersing the Fe3O4@SC composite in ethylene glycol, adding cobalt acetate and thiourea, ultrasonically dispersing, and then hydrothermally reacting at 180-220°C, separating the solid and liquid phases of the reaction product, washing and drying to obtain the sulfur-vacancy-rich cobalt-sulfur bimetallic composite material CoS / Fe3O4@SC; this material has the advantages of high catalytic activity, excellent magnetic separation performance, and good structural stability, and is rich in oxygen vacancies (Ov) and sulfur vacancies (Sv) double defects, and can be widely used to degrade new pollutants with good degradation and removal effects.

[0007] The mass ratio of oxalic acid to soluble starch is 35-40:1; the mass ratio of ferrous sulfate to oxalic acid is 1-1.5:1; the mass ratio of thiourea to cobalt acetate is 0.02-0.04:1; and the mass ratio of thiourea to Fe3O4@SC complex is 0.05-0.1:1.

[0008] Another objective of this invention is to apply sulfur-vacancy-rich cobalt-sulfur bimetallic composite materials to the degradation of tetracycline hydrochloride, chlortetracycline, oxytetracycline, methylene blue, methyl orange, and Congo red.

[0009] Compared with the prior art, the present invention has the following advantages: (1) In this invention, soluble starch is used as a dispersant and carbon source. Through a co-precipitation-aging coupled high-temperature pyrolysis strategy, Fe3O4 nanoparticles are highly dispersed on a carbon matrix, which effectively inhibits particle aggregation and increases the exposure of active sites. (2) This invention constructs an Fe / Co bimetallic synergistic catalytic system by uniformly loading CoS nanoparticles onto the surface of the Fe3O4@SC composite using a one-step hydrothermal method. The low-valence sulfur species in CoS possess strong reducing power and can act as electron donors to accelerate the reduction of Co. 3+ / Co 2+ with Fe 3+ / Fe 2+ The redox cycle significantly enhances the sustained activation ability of PMS. The high-temperature pyrolysis process induces a large number of oxygen vacancies (Ov), while simultaneously introducing sulfur vacancies (Sv) into the CoS lattice. The synergistic effect of these two vacancies significantly lowers the PMS decomposition activation barrier, promoting the activation of singlet oxygen (Ov). 1 The selective generation of O2 makes the reaction dominated by non-radical pathways, giving it excellent resistance to interference from inorganic anions. (3) The sulfur-rich cobalt bimetallic composite material prepared by the present invention can effectively degrade the new pollutants when mixed with them under constant temperature and vibration conditions. It has the advantages of simple preparation method, controllable operation, wide availability of raw materials, and easy industrial scale-up production. Attached Figure Description

[0010] Figure 1 XRD patterns for different catalysts; Figure 2 Figure c shows SEM images of different catalysts and surface elemental distribution diagrams of CoS / Fe3O4@SC, where Figures a and d are Fe3O4@SC; and Figures b and e are CoS / Fe3O4@SC. Figure 3 EPR diagrams for different catalysts; Figure 4 The TC degradation rate (a) and the corresponding kinetic constant (b) are for different catalysts. Figure 5 The effect of inorganic anions on catalytic performance (a) and the corresponding kinetic constants (b); Figure 6 Removal of different dyes and antibiotics (a) and corresponding kinetic constants (b); Figure 7 The results are from five cycles of CoS / Fe3O4@SC degradation in TC. Detailed Implementation

[0011] The following examples further illustrate the content of the present invention, but these examples do not limit the scope of protection of the present invention. Unless otherwise specified, the methods in the examples are conventional methods, and the reagents used are commercially available reagents unless otherwise specified. Example 1: Preparation of sulfur-cobalt bimetallic composite material rich in sulfur vacancies 1. Dissolve 5.264 g of H₂C₂O₄·2H₂O and 0.14 g of soluble starch in 200 mL of deionized water, denoted as solution A. Stir the solution in a 60 °C water bath for 30 min. Separately, weigh 5.56 g of FeSO₄·7H₂O and dissolve it in 100 mL of deionized water, denoted as solution B. Add solution B dropwise to solution A under stirring at 60 °C, and then continue aging at 60 °C for 2 h. After the reaction is complete, collect the solid product, wash it first with deionized water, then with anhydrous ethanol, alternating between the two processes several times. Filter to obtain the ferrous oxalate precursor, and then dry it in a 60 °C oven for 12 h. Transfer the dried precursor to an open crucible, place it in a tube furnace, and calcine it at 500 °C at a rate of 5 °C / min under a nitrogen atmosphere for 2 h to obtain the Fe₃O₄@SC composite. The XRD pattern of the Fe₃O₄@SC composite is shown below. Figure 1The main diffraction peaks of Fe3O4@SC are located at 18.3° (111), 30.1° (220), 35.5° (311), 37.2° (222), 43.1° (400), 53.5° (400), 57.0° (511), 62.6° (440), and 74.1° (533), which are in good agreement with the standard peaks of Fe3O4 (JCPDS: 88-0866), indicating the successful synthesis of Fe3O4. Since the generated carbon is an amorphous phase, no unique characteristic diffraction peaks were observed. The SEM image of Fe3O4@SC is shown below. Figure 2 a and 2d have a cuboid morphology and a loose and rough surface structure. This unique surface morphology and microstructure are conducive to exposing more active sites, providing more favorable conditions for catalytic reactions.

[0012] 2. Weigh 0.373 g Co(AC)₂·4H₂O and 0.14 g Fe₃O₄@SC, add them to 50 mL ethylene glycol, and sonicate for 30 min to ensure thorough dispersion. Then add 0.0114 g thiourea, and continue sonicating for another 30 min. Transfer the mixed solution to a reaction vessel and hydrothermally react at 200℃ for 24 h. After the reaction is complete, collect the solid product, wash it first with deionized water, then with anhydrous ethanol, alternating between the two processes three times. After filtration and drying, a sulfur-vacancy-rich cobalt-sulfur bimetallic composite material CoS / Fe₃O₄@SC is obtained. The SEM image of CoS / Fe₃O₄@SC is shown below. Figure 2 b and Figure 2 e, still retaining a cuboid structure, but its surface is uniformly covered with sheet-like, wrinkled CoS. Simultaneously, EDS analysis of the elements in CoS / Fe3O4@SC revealed that the CoS / Fe3O4@SC sample contains only Co, S, Fe, O, and C, with Co and S elements uniformly distributed on the Fe3O4@SC. This indicates the successful synthesis of CoS / Fe3O4@SC. Figure 2 c). Co and S are the key active centers for activating PMS. They exhibit a high-density and uniform distribution on the CoS / Fe3O4@SC surface, which is beneficial for fully exerting their catalytic effect and improving material performance; XRD pattern of sulfur-vacancy-rich cobalt-sulfur bimetallic composite CoS / Fe3O4@SC is shown below. Figure 1 The diffraction peaks of CoS / Fe3O4@SC in the figure show the simultaneous appearance of characteristic diffraction peaks of CoS (JCPDS: 01-1279) and Fe3O4 (JCPDS: 88-0688), proving the successful preparation of CoS / Fe3O4@SC. The diffraction signal of CoS is relatively weak, which is mainly attributed to its low crystallinity.

[0013] EPR testing of the sulfur-vacancy-rich cobalt-sulfur bimetallic composite CoS / Fe3O4@SC is shown in [reference needed]. Figure 3 At g=2.003, both Fe3O4@SC and CoS exhibited strong electron paramagnetic resonance (EPR) signals, confirming the presence of abundant Ov in Fe3O4@SC and abundant Sv in CoS. The EPR signal intensity of the CoS / Fe3O4@SC sample was significantly higher than that of the Fe3O4@SC and CoS samples alone, indicating the presence of more unpaired electrons. This also confirms the coexistence of Ov and Sv in the CoS / Fe3O4@SC composite material. The abundant vacancy defects facilitate the exposure of more metal active centers (Fe, Co) in the PMS activation reaction of CoS / Fe3O4@SC, thereby enhancing its catalytic performance.

[0014] Comparative Example 1: The Fe3O4@SC complex prepared in step 1 of Example 1 was used as a catalyst; Example 2: Experiment on the treatment of pollutants by the catalyst in Example 1 and Comparative Example 1 1. Under experimental conditions of 0.2 g / L catalyst, 2.5 mM PMS persulfate, pH 4.2 (i.e., the initial pH of the tetracycline hydrochloride (TC) solution), and 50 mg / L TC concentration, the catalytic degradation performance of TC by the CoS / Fe3O4@SC composite catalyst of Example 1 and the Fe3O4@SC composite catalyst of Comparative Example 1 was compared. At reaction times of 1, 2, 3, 4, and 5 min, appropriate amounts of reaction solution were drawn using a syringe equipped with a 0.22 µm microporous filter head, filtered, and clarified. The filtrate was placed in a cuvette, and its absorbance at the characteristic wavelength of TC (364 nm) was measured using a UV-Vis spectrophotometer. The corresponding reaction solution concentration was calculated based on the standard curve.

[0015] See results Figure 4 a. In 5 minutes, the CoS / Fe3O4@SC composite material achieved a 100% degradation rate of TC, significantly outperforming other control materials. This superior catalytic performance is partly due to Fe 2+ / Fe 3+ With Co 2+ / Co 3+ The rapid electron cycling significantly improves the PMS activation efficiency; on the other hand, the carbon layer structure in the catalyst inhibits the highly active component Co. 2+ Dissolution.

[0016] The dynamic fitting results are shown in Figure 4 b, the apparent rate constant of CoS / Fe3O4@SC ( k The highest value was 1.098 min. -1 It is Fe3O4@SC (0.0404 min) -1This is 27.18 times that of the previous method. This indicates that CoS / Fe3O4@SC has a significant catalytic advantage in activating PMS to degrade TC.

[0017] 2. The effects of different anions on the degradation rate of TC were investigated under the experimental conditions of step 1. Cl was selected. - NO3 - CO3 2- SO4 2- and H2PO4 - Five common anions (all at a concentration of 10 mM) were studied. The results are as follows: Figure 5 As shown in figure a, Cl was added. - NO3 - CO3 2- SO4 2- and H2PO4 - Afterwards, the degradation rates of TC were 87.48%, 100%, 88.47%, 100%, and 100%, respectively. Compared with the blank control group without added anions, the addition of Cl... - and CO3 2- The degradation rate of TC decreased slightly afterward. Figure 5 As shown in b, the degradation data of TC under the blank group and under various anion addition conditions were fitted, and the first-order kinetic constant values ​​were obtained as 1.098 min. -1 (Blank), 0.314min -1 (Cl) - ), 1.276min -1 (NO3) - ), 0.282min -1 (CO3) 2- ), 1.377min -1 (SO4) 2- ) and 1.235min -1 (H2PO4) - Therefore, it can be seen that adding NO3... - SO4 2- and H2PO4 - The degradation rate of TC was not affected but increased. This may be because these anions can participate in the formation of more active intermediate species or synergistically promote the generation of reactive oxygen species during PMS activation, thereby enhancing the oxidative degradation effect on TC.

[0018] 3. Under the experimental conditions described in step 1, the degradation concentration was 50 mg·L⁻¹. -1 The general applicability of the CoS / Fe3O4@SC / PMS system was investigated using different dyes and antibiotics. The results are as follows: Figure 6As shown in figure a, the removal rates of tetracycline hydrochloride (TC), chlortetracycline (CTC), oxytetracycline (OTC), methylene blue (MB), methyl orange (MO), and Congo red (CR) by CoS / Fe3O4@SC were 94.28%, 100.0%, 100%, 100%, 100%, and 100%, respectively. This system achieved 100% degradation of multiple dyes within a short time (5 min), indicating that CoS / Fe3O4@SC has strong oxidizing power and a broad substrate applicability. Figure 6 As shown in b, the corresponding pseudo-first-order reaction kinetic constants are 0.511 min. -1 1.098min -1 1.241min -1 2.508 min -1 4.605min -1 and 8.151min -1 This indicates that the CoS / Fe3O4@SC / PMS system exhibits good adaptability and efficient catalytic degradation capability for pollutants with different structural types (including TCs and anionic / cationic dyes), demonstrating its broad application potential in organic wastewater treatment.

[0019] To evaluate the cycling stability of CoS / Fe3O4@SC, the catalyst CoS / Fe3O4@SC used in step 1 was collected, washed and dried with deionized water, and then recycled to TC wastewater according to the method in step 1. Four consecutive repeated degradation experiments were conducted, and the results are as follows. Figure 7 As shown, after five cycles, the degradation rate of TC by the CoS / Fe3O4@SC / PMS system decreased by only about 10% compared to the first use, indicating that the catalytic performance remained good. The TC degradation rate still reached 90.08% after the fifth cycle, demonstrating that CoS / Fe3O4@SC has good structural stability and recyclability, and possesses good application potential in practical water treatment.

Claims

1. A sulfur-cobalt bimetallic composite material rich in sulfur vacancies, characterized in that: Oxalic acid, soluble starch, and deionized water were mixed and stirred at 55-65℃. Then, ferrous sulfate solution was added dropwise, and the mixture was aged in a water bath at 55-65℃. The solid and liquid were separated, and the solid product was washed and dried to obtain a starch-containing ferrous oxalate precursor. The precursor was calcined at 450-550℃ for 1-3 h in a nitrogen atmosphere to obtain the Fe3O4@SC composite. The Fe3O4@SC composite was dispersed in ethylene glycol, and cobalt acetate and thiourea were added. After ultrasonic dispersion, the mixture was hydrothermally reacted at 180-220℃. The reaction product was separated into solid and liquid phases, washed and dried to obtain the sulfur-vacancy-rich cobalt sulfur bimetallic composite material CoS / Fe3O4@SC.

2. The sulfur-vacancy-rich sulfur-cobalt bimetallic composite material according to claim 1, characterized in that: The mass ratio of oxalic acid to soluble starch is 35-40:1; the mass ratio of ferrous sulfate to oxalic acid is 1-1.5:

1.

3. The sulfur-vacancy-rich sulfur-cobalt bimetallic composite material according to claim 1, characterized in that: The mass ratio of thiourea to cobalt acetate is 0.02-0.04:1, and the mass ratio of thiourea to Fe3O4@SC complex is 0.05-0.1:

1.

4. The use of the sulfur-vacancy-rich sulfur-cobalt bimetallic composite material according to any one of claims 1-3 in the degradation of tetracycline hydrochloride, chlortetracycline, oxytetracycline, methylene blue, methyl orange and Congo red.